2014
DOI: 10.5539/jas.v6n2p170
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Optimal Land Use Allocation Among Small Holder (A1) Farmer Households in Zimbabwe. A Case Study of Long Croft Farm, in Mazowe District

Abstract: This study aimed to develop an optimal land use plan for Long Croft farm (LCF) by assessing the available land resources. It evaluates the potential of the land resources for recommending optimum, sustainable and appropriate land utilisation in agriculture development. Possible ways in improving farming systems and more efficient utilization of the scarce available agricultural resources especially arable land were determined. The study used quantitative analytical approach in optimal land use allocation analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(16 reference statements)
0
4
0
1
Order By: Relevance
“…Most of the literatures reviewed here are articles that used linear programming decision support systems for crop mix and cropping pattern (65%) while the remaining are articles that employed linear programming to promote the performance of dairy farms, crop-livestock integration, land and water resource use, arable crops and fisheries enterprises, botanical farm, and other forms of land use with the aim of maximizing net income, maximizing gross income, improving food security, and enhancing livelihood performance. Outlined results suggested that using LP as decision making tool in agriculture provides maximum annual return (Sarker et al, 1997;Hassan et al, 2005;Fallah Shamsi, 2010;Mohamad and Said, 2011;Alabdulkader et al, 2012;Felix et al, 2013;Geta et al, 2013;Andreea and Adrian, 2013;Gadge et al, 2014;Mugabe et al, 2014;Buzuzi and Buzuzi, 2018;Muhammed Jaslam et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the literatures reviewed here are articles that used linear programming decision support systems for crop mix and cropping pattern (65%) while the remaining are articles that employed linear programming to promote the performance of dairy farms, crop-livestock integration, land and water resource use, arable crops and fisheries enterprises, botanical farm, and other forms of land use with the aim of maximizing net income, maximizing gross income, improving food security, and enhancing livelihood performance. Outlined results suggested that using LP as decision making tool in agriculture provides maximum annual return (Sarker et al, 1997;Hassan et al, 2005;Fallah Shamsi, 2010;Mohamad and Said, 2011;Alabdulkader et al, 2012;Felix et al, 2013;Geta et al, 2013;Andreea and Adrian, 2013;Gadge et al, 2014;Mugabe et al, 2014;Buzuzi and Buzuzi, 2018;Muhammed Jaslam et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Program linier dapat digunakan untuk memaksimalkan laba berdasarkan pada keterbatasan luas lahan, jam kerja buruh tani, modal dan tingkat konsumsi. Seluruh keterbatasan tersebut merupakan fungsi konstrain (Mugabe et al, 2014).…”
Section: Aditivitas : Setiap Fungsi Program Linierunclassified
“…The LP model was estimated for the combined sample subject to the ecological constraint [23,28] that land allocated not exceed the total land suitable for selected crops in the community (estimated from survey data) and with the financial constraint [29][30][31] that total expenditures not exceed the sum of households' total crop budgets (the total sum of money budgeted and paid to cover the cost of production of selected crops by each individual surveyed households, except land rent and wage of family labor in the 2012 July to September cropping season). Finally, we imposed an additional food crop production self-sufficiency constraint for each of the selected crops, reflecting the aggregated minimum food crop production requirement set by each household surveyed.…”
Section: Profit Maximizing Objectivementioning
confidence: 99%